Characterization of Magnetic Minerals of Iron Sand Pasia Nan Tigo Padang Beach Using X-Ray Diffraction (XRD) - Ardilla Nofri Yuwanda; Riza Rahmayuni; Dwi Anisa Visgun; Anisa Rahmi; Hamdi Rifai; Letmi Dwiridal (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
The mineral extraction of iron sand from Pasia Nan Tigo Beach has been carried out. Iron sands in this area are widely spread and have decent potential but have not been used optimally. The iron sand of Pasia Nan Tigo Beach contains minerals that are indicated by the variation in susceptibility values of type 265.8×10-8m3/kg to 12,445.53×10-8m3/kg. Therefore, it is necessary to separate minerals from iron sand so that the minerals contained in them are known so that they are suitable for usability. The iron sand obtained is extracted using two magnets, namely a strong magnet and a weak magnet. The extraction results from iron sand still contain impurities to remove them, the sand is purified and then the sand extraction results are characterized using the XRD method. Content The type and structure of the mineral species found in the samples extracted from iron sand using strong magnets are Magnetite (Fe3O4) with Cubic structure, Hematite (α-Fe2O3) with Hexagonal structure, and Ilmenite (FeTiO3) with Hexagonal structure. While the use of weak magnets is Magnetite (Fe3O4) with Cubic structure, Hematite (α-Fe2O3) with Rhombohedral structure, and Ilmenite (FeTiO3) with Rhombohedral structure. Meanwhile, the non-magnetic mineral namely Quartz (SiO2), works as an impurity. The average crystal size using a strong magnet for PNT-B01 0-5 cm is 100.85 nm and a weak magnet is 49.36 nm, sample A06 30-35 cm uses a strong magnet of 88.25 nm and a weak magnet of 46, 80 nm, meanwhile sample B10 0-5 cm with a strong magnet of 109.22 nm and a weak magnet of 45.60 nm.